Preparation method of anti-dispersion shield grouting material
By carboxylation modification of fly ash of shield grouting materials and introducing modified cyanate ester and polydopamine modified carbon fibers, the problems of low stone rate, high water excretion rate and poor compressive strength of shield grouting materials are solved, and the stone rate of the material is improved, reducing water excretion rate and guaranteed compressive strength.
Patent Information
- Application Number
- CN202510067936.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-25
AI Technical Summary
The existing shield grouting materials have problems such as low stone rate, high water secretion rate and poor compressive strength, which affect their practical application.
By carboxylation modification of fly ash, the main raw material of the grouting material, and introducing modified components such as modified cyanate and polydopamine modified carbon fiber, a dispersive shield grouting material was prepared.
It effectively improves the stone rate of the material, reduces the water secretion rate, ensures good compressive strength, and improves the anti-dispersion performance.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of grouting materials, and in particular relates to a method for preparing an anti-dispersion shield grouting material. Background Art
[0002] During shield construction, the surrounding soil will be disturbed, especially when the segment is about to come out of the tail shield, an annular gap will be formed between the segment tunnel and the surrounding soil; tunnel synchronous grouting can make the stratum and the segment lining fit together tightly, and the surrounding stratum will produce uniform pressure on the segment lining through the early strength of the grouting layer, thus improving the structural safety of the segment lining. Shield grouting materials are important materials used in the shield construction process to fill the gaps around the tunnel, stabilize the stratum, prevent groundwater leakage, and provide early support. Shield grouting technology is crucial to ensure the safety and quality of tunnel construction.
[0003] A Chinese patent (publication number CN115872676A) discloses a vibration-resistant and tough shield tunnel synchronous grouting material and a preparation method thereof, comprising 400-500 parts of a base material, 5-22.8 parts of a composite toughening admixture, and 250-350 parts of water, wherein the base material is composed of the following components in parts by weight: 30-50 parts of cement, 40-70 parts of mineral powder, 60-100 parts of steel slag powder, 45-85 parts of rice husk ash, 100-180 parts of fly ash, and 70-110 parts of machine-made sand; the composite toughening admixture is composed of the following components in parts by weight: 0.2-1 parts of carbon fiber, 0.4-2 parts of steel fiber, 0.2-0.8 parts of polypropylene fiber, and 4-20 parts of biomass ash. The grouting material has good anti-vibration performance, excellent mechanical properties, and high fold-to-compression ratio, which is conducive to reducing cracks in the stone body, improving the overall mechanical properties, durability and impermeability of the shield tunnel, and realizing safe construction and operation of the shield tunnel. However, the patent does not solve the problem that the shield grouting material in the prior art has a low stone rate, a high water seepage rate, and poor compressive strength resulting in poor anti-dispersion performance, which seriously affects its practical application.
[0004] Therefore, how to modify the fly ash, the main raw material of the grouting material, and introduce different modified components to prepare anti-dispersion shield grouting material, effectively improve the stone rate of the material, reduce the water seepage rate, and ensure good compressive strength has become a direction that needs to be focused on. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing an anti-dispersion shield grouting material, aiming to solve the problems of low stone rate, high water seepage rate and poor compressive strength resulting in poor anti-dispersion performance of the shield grouting material in the prior art.
[0006] The present invention prepares the anti-dispersion shield grouting material by subjecting the main raw material fly ash of the grouting material to carboxyl modification treatment and introducing modified components such as modified cyanate ester and polydopamine modified carbon fiber, thereby effectively improving the stone rate of the material, reducing the water bleeding rate and ensuring good compressive strength.
[0007] The technical solution adopted by the present invention to solve the above technical problems is as follows:
[0008] The present invention provides a method for preparing an anti-dispersion shield grouting material, comprising the following steps:
[0009] Step S1: by weight, 2 to 4 parts of silane coupling agent KH550 and 2 to 4 parts of succinic anhydride are added to 180 to 200 parts of N,N-dimethylformamide and stirred for 2 to 4 hours, then 40 to 50 parts of fly ash are added and stirred for reaction for 4 to 6 hours, and after the reaction is completed, the mixture is dried to obtain carboxylated fly ash;
[0010] Step S2: adding 160 to 200 parts of cement, 15 to 20 parts of epoxy resin, 4 to 8 parts of cyanate ester and 4 to 6 parts of carbon fiber to 480 to 500 parts of deionized water, stirring for 40 to 60 minutes, and then adding 1 to 3 parts of water reducer, 1 to 3 parts of defoamer, and 0.6 to 0.8 parts of thickener and stirring for 20 to 30 minutes to obtain a premixed system;
[0011] Step S3: In parts by weight, 360 to 400 parts of the carboxylated fly ash, 100 to 140 parts of mineral powder and 20 to 24 parts of bentonite are added to 480 to 500 parts of the premixed system and stirred to obtain an anti-dispersion shield grouting material.
[0012] After the carboxylated fly ash is modified, the surface of the fly ash particles carries more carboxyl functional groups. The surface carboxyl groups can form stronger interfacial bonding forces with the hydration products of the grouting materials through hydrogen bonds, electrostatic effects or chemical bonds, thereby improving the overall strength and density through strong interfacial bonding forces, thereby increasing the stone rate of the grouting material.
[0013] As a preferred technical solution of the present invention, the epoxy resin is bisphenol A type epoxy resin and biphenyl type epoxy resin.
[0014] As a preferred technical solution of the present invention, the mass ratio of the bisphenol A epoxy resin to the biphenyl epoxy resin is (1-2):1.
[0015] As a preferred technical solution of the present invention, the cyanate ester is a modified cyanate ester; the preparation method of the modified cyanate ester comprises: adding 6 to 10 parts of 3-aminopropyltriethoxysilane to 80 to 100 parts of deionized water by weight and stirring evenly, then adding 50 to 60 parts of talc and stirring for 40 to 60 minutes, drying to obtain modified talc; mixing 90 to 100 parts of cyanate ester, 10 to 12 parts of the modified talc and 4 to 6 parts of ethyl acetate, first stirring and dispersing for 20 to 30 minutes, and then ultrasonically dispersing for 40 to 60 minutes to obtain the modified cyanate ester.
[0016] Talc is introduced into the modified cyanate ester. The fine particles of talc can fill the gaps between the cyanate ester resin and other ingredients to form a denser structure, preventing water from separating from the slurry. At the same time, the layered structure of talc can be physically cross-linked with the cyanate ester molecules to form a denser network structure, thereby effectively reducing the water seepage rate.
[0017] As a preferred technical solution of the present invention, the carbon fiber is a polydopamine modified carbon fiber; the preparation method of the polydopamine modified carbon fiber comprises: in parts by weight, 40 to 50 parts of anhydrous ethanol and 40 to 50 parts of acetone are mixed evenly, and then 10 to 20 parts of carbon fiber are added to soak for 20 to 24 hours, and after the soaking is completed, the carbon fiber is washed with deionized water and dried to obtain a pretreated carbon fiber; 16 to 20 parts of trishydroxymethylaminomethane and 6 to 8 parts of dopamine hydrochloride are added to 300 to 400 parts of deionized water and stirred for 40 to 60 minutes, and then 10 to 20 parts of the pretreated carbon fiber are added to soak for 12 to 16 hours, and after the soaking is completed, the carbon fiber is vacuum dried to obtain the polydopamine modified carbon fiber.
[0018] As a preferred technical solution of the present invention, the diameter of the carbon fiber is 100-400 nm.
[0019] A large number of amino groups and phenolic hydroxyl groups are introduced into the surface of polydopamine-modified carbon fiber, which improves the wettability of the carbon fiber surface. By forming chemical bonds with the matrix, the interfacial adhesion is enhanced, which can better transfer stress and effectively increase the compressive strength of the grouting material.
[0020] As a preferred technical solution of the present invention, the water reducer is selected from any one of polycarboxylate water reducer, melamine water reducer and naphthalene water reducer or a combination of at least two thereof.
[0021] As a preferred technical solution of the present invention, the defoaming agent is selected from any one of tributyl phosphate, polydimethylsiloxane, and tripolyglycerol monostearate, or a combination of at least two thereof.
[0022] As a preferred technical solution of the present invention, the thickener is selected from any one of hydroxypropyl methylcellulose, polyvinyl pyrrolidone, and polyacrylamide, or a combination of at least two thereof.
[0023] As a preferred technical solution of the present invention, the stirring treatment conditions include: stirring at 800-1000 rpm for 10-20 min.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The modified cyanate ester of the present invention is used as a curing agent for epoxy resin and can form a first cross-linking network with the epoxy resin during the curing process; at the same time, the modified cyanate ester is modified to introduce talc containing amino groups, so it contains active groups such as cyanate groups and amino groups, wherein the amino groups can combine with carboxylated fly ash, and the cyanate groups can react with the phenolic hydroxyl groups of polydopamine-modified carbon fibers by nucleophilic addition reaction. Based on the modified cyanate ester, the carboxylated fly ash and the polydopamine-modified carbon fibers are connected in series to construct a second cross-linking network; at the same time, the combined effect of the first cross-linking network and the second cross-linking network effectively improves the stone formation rate of the grouting material, reduces the water bleeding rate, and ensures good compressive strength.
[0026] (2) After the carboxylated fly ash of the present invention is modified, the surface of the fly ash particles has more carboxyl functional groups. The surface carboxyl groups can form stronger interfacial bonding forces with cement hydration products through hydrogen bonds, electrostatic effects or chemical bonds, thereby improving the overall strength and density through strong interfacial bonding forces, thereby increasing the stone rate of the grouting material.
[0027] (3) Talc is introduced into the modified cyanate ester of the present invention. The fine particles of talc can fill the gaps between the cyanate ester resin and other components to form a denser structure, thereby preventing water from separating from the slurry. At the same time, the layered structure of talc can be physically cross-linked with the cyanate ester molecules to form a denser network structure, thereby effectively reducing the water bleeding rate.
[0028] (4) A large number of amino groups and phenolic hydroxyl groups are introduced into the surface of the polydopamine-modified carbon fiber of the present invention, which improves the wettability of the carbon fiber surface. By forming chemical bonds with the matrix, the interfacial adhesion is enhanced, which can better transfer stress, thereby effectively increasing the compressive strength of the grouting material. DETAILED DESCRIPTION
[0029] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0030] The sources of some components in the embodiments and comparative examples are as follows:
[0031] Cement, product number CA-75, was purchased from Zhengzhou Kerui (Group) Refractory Materials Co., Ltd.;
[0032] Mineral powder, item number 6-9444, was purchased from Lingshou County Zhenying Mineral Products Processing Plant;
[0033] Fly ash, product number A01085, was purchased from Wuhan Jiyesheng Chemical Co., Ltd.;
[0034] Bentonite, CAS No. 1302-78-9, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0035] Bisphenol A epoxy resin, product number jER828EL, was purchased from Mitsubishi Chemical Corporation;
[0036] Biphenyl type epoxy resin, product number NC-3000-L, purchased from Nippon Kayaku Co., Ltd.
[0037] Cyanate ester, product number MDI50, purchased from Wanhua Chemical Company;
[0038] Carbon fiber I, model VGCF, fiber diameter 200 nm, purchased from Zhongke Leiming (Beijing) Technology Co., Ltd.;
[0039] Carbon fiber II, model SYT45S-12K, fiber diameter 7 μm, purchased from Shenzhen Jusheng Carbon Fiber Co., Ltd.;
[0040] Polycarboxylate water reducer, model ZWL-A-Ⅸ, purchased from Zhejiang Wulong Chemical Co., Ltd.;
[0041] Melamine water reducing agent, model VF-8, purchased from Shanghai Luke Chemical Co., Ltd.;
[0042] Naphthalene-based water reducer, model SNF-A, purchased from Shenyang Xingzhenghe Chemical Co., Ltd.;
[0043] Tributyl phosphate, CAS No. 126-73-8, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0044] Polydimethylsiloxane, CAS No. 9006-65-9, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0045] Triglycerol monostearate, CAS No. 26855-43-6, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0046] Hydroxypropyl methylcellulose, product number H108814, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0047] Polyvinyl pyrrolidone, product number PA73670, was purchased from Shanghai Chuangsai Technology Co., Ltd.;
[0048] Polyacrylamide, product number P108471, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0049] Silane coupling agent KH550, product number RB1032, was purchased from Shanghai Huicheng Biotechnology Co., Ltd.;
[0050] Succinic anhydride, CAS No. 108-30-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0051] N,N-dimethylformamide, CAS number 68-12-2, purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0052] 3-Aminopropyltriethoxysilane, CAS No. 919-30-2, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0053] Talc, product number T109494, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0054] Ethyl acetate, CAS No. 141-78-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0055] Anhydrous ethanol, CAS No. 64-17-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0056] Acetone, CAS No. 67-64-1, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0057] Tris(hydroxymethyl)aminomethane, CAS No. 77-86-1, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0058] Dopamine hydrochloride, CAS No. 62-31-7, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0059] Preparation of modified cyanate ester: by weight, 10 parts of 3-aminopropyltriethoxysilane are added to 100 parts of deionized water and stirred evenly, then 60 parts of talc are added and stirred for 60 minutes, and dried to obtain modified talc; 100 parts of cyanate ester, 12 parts of the modified talc and 6 parts of ethyl acetate are mixed, first stirred and dispersed for 30 minutes, and then ultrasonically dispersed for 60 minutes to obtain the modified cyanate ester.
[0060] Preparation of polydopamine modified carbon fiber: In parts by weight, 50 parts of anhydrous ethanol and 50 parts of acetone are mixed evenly, and then 20 parts of carbon fiber I (fiber diameter is 200nm) are added and immersed for 24 hours. After the immersion is completed, it is washed with deionized water and dried to obtain pretreated carbon fiber; 20 parts of trihydroxymethylaminomethane and 8 parts of dopamine hydrochloride are added to 400 parts of deionized water and stirred for 60 minutes, and then 20 parts of the pretreated carbon fiber are added and immersed for 16 hours. After the immersion is completed, it is vacuum dried to obtain the polydopamine modified carbon fiber.
[0061] Example 1
[0062] This embodiment provides a method for preparing an anti-dispersion shield grouting material, comprising the following steps:
[0063] Step S1: In parts by weight, 4 parts of silane coupling agent KH550 and 4 parts of succinic anhydride are added to 200 parts of N,N-dimethylformamide and stirred for 4 hours, and then 50 parts of fly ash are added and stirred for reaction for 6 hours. After the reaction is completed, the mixture is dried to obtain carboxylated fly ash;
[0064] Step S2: In parts by weight, 200 parts of cement, 20 parts of epoxy resin (10 parts of bisphenol A epoxy resin and 10 parts of biphenyl epoxy resin), 8 parts of modified cyanate ester and 6 parts of polydopamine modified carbon fiber are added to 500 parts of deionized water and stirred for 60 minutes, and then 3 parts of polycarboxylic acid water reducer, 3 parts of defoaming agent tributyl phosphate, and 0.8 parts of thickener hydroxypropyl methylcellulose are added and stirred for 30 minutes to obtain a premixed system;
[0065] Step S3: In parts by weight, 400 parts of the carboxylated fly ash, 140 parts of mineral powder and 24 parts of bentonite are added to 500 parts of the premixed system for stirring, and stirred at 1000 rpm for 20 minutes to obtain an anti-dispersion shield grouting material.
[0066] Example 2
[0067] This embodiment provides a method for preparing an anti-dispersion shield grouting material, comprising the following steps:
[0068] Step S1: by weight, 2 parts of silane coupling agent KH550 and 2 parts of succinic anhydride are added to 180 parts of N,N-dimethylformamide and stirred for 2 hours, then 40 parts of fly ash are added and stirred for reaction for 4 hours, and after the reaction is completed, the mixture is dried to obtain carboxylated fly ash;
[0069] Step S2: In parts by weight, 160 parts of cement, 15 parts of epoxy resin (10 parts of bisphenol A epoxy resin and 5 parts of biphenyl epoxy resin), 4 parts of modified cyanate ester and 4 parts of polydopamine modified carbon fiber are added to 480 parts of deionized water and stirred for 40 minutes, and then 1 part of melamine water reducer, 1 part of defoamer polydimethylsiloxane, and 0.6 part of thickener polyvinyl pyrrolidone are added and stirred for 20 minutes to obtain a premixed system;
[0070] Step S3: In parts by weight, 360 parts of the carboxylated fly ash, 100 parts of mineral powder and 20 parts of bentonite are added to 480 parts of the premixed system for stirring, and stirred at 800 rpm for 10 minutes to obtain an anti-dispersion shield grouting material.
[0071] Example 3
[0072] This embodiment provides a method for preparing an anti-dispersion shield grouting material, comprising the following steps:
[0073] Step S1: by weight, 3 parts of silane coupling agent KH550 and 3 parts of succinic anhydride were added to 190 parts of N,N-dimethylformamide and stirred for 3 hours, and then 45 parts of fly ash were added and stirred for reaction for 5 hours. After the reaction was completed, the mixture was dried to obtain carboxylated fly ash;
[0074] Step S2: In parts by weight, 180 parts of cement, 18 parts of epoxy resin (10 parts of bisphenol A epoxy resin and 8 parts of biphenyl epoxy resin), 6 parts of modified cyanate ester and 5 parts of polydopamine modified carbon fiber are added to 490 parts of deionized water and stirred for 50 minutes, and then 2 parts of naphthalene-based water reducer, 1 to 3 parts of defoamer tripolyglycerol monostearate and 0.7 parts of thickener polyacrylamide are added and stirred for 25 minutes to obtain a premixed system;
[0075] Step S3: In parts by weight, 380 parts of the carboxylated fly ash, 120 parts of mineral powder and 22 parts of bentonite are added to 490 parts of the premixed system for stirring, and stirred at 900 rpm for 15 minutes to obtain an anti-dispersion shield grouting material.
[0076] Comparative Example 1
[0077] This comparative example provides a preparation process of a grouting material, which differs from Example 1 in that commercially available fly ash is used instead of carboxylated fly ash.
[0078] Comparative Example 2
[0079] This comparative example provides a preparation process of a grouting material, which is different from Example 1 in that the amount of bisphenol A epoxy resin is changed to 16 parts, and the amount of biphenyl epoxy resin is changed to 4 parts.
[0080] Comparative Example 3
[0081] This comparative example provides a preparation process of a grouting material, which is different from Example 1 in that the amount of bisphenol A epoxy resin is changed to 4 parts, and the amount of biphenyl epoxy resin is changed to 16 parts.
[0082] Comparative Example 4
[0083] This comparative example provides a preparation process of a grouting material, which differs from Example 1 in that commercially available cyanate ester is used instead of modified cyanate ester.
[0084] Comparative Example 5
[0085] This comparative example provides a preparation process of a grouting material, which differs from Example 1 in that carbon fiber I is used instead of polydopamine-modified carbon fiber.
[0086] Comparative Example 6
[0087] This comparative example provides a preparation process of a grouting material, which differs from Example 1 in that carbon fiber II is used instead of carbon fiber I to prepare polydopamine-modified carbon fiber.
[0088] The performance of the grouting materials provided in the above embodiments and comparative examples was tested, and the specific testing method is as follows:
[0089] (1) Stone rate test: The test is conducted in accordance with the requirements of T / CECS 563-2018 Technical Specification for Application of Synchronous Grouting Materials for Shield Tunneling.
[0090] (2) Water seepage rate test: The test shall be conducted in accordance with the requirements of T / CECS 563-2018 Technical Specification for Application of Synchronous Grouting Materials for Shield Tunnels.
[0091] (3) Compressive strength test: The test shall be conducted in accordance with the requirements of DB42 / T 1218-2016 Synchronous Grouting Materials for Shield Tunneling.
[0092] The above performance test data is shown in Table 1.
[0093] Table 1 Performance test results
[0094] Stone rate (%) Water seepage rate (%) 28d compressive strength (MPa) Example 1 97.72 1.43 9.75 Example 2 97.53 1.65 9.54 Example 3 97.65 1.57 9.63 Comparative Example 1 91.84 3.67 4.48 Comparative Example 2 93.86 2.54 6.54 Comparative Example 3 94.01 2.46 6.67 Comparative Example 4 91.98 3.52 4.63 Comparative Example 5 92.13 3.59 4.71 Comparative Example 6 94.35 2.33 6.89
[0095] From the above content, it can be seen that the present invention prepares anti-dispersion shield grouting material (Example 1 to Example 3) by carboxylating the main raw material fly ash of the grouting material and introducing modified components such as modified cyanate and polydopamine modified carbon fiber. The stone rate is 97.53-97.72%, the water seepage rate is 1.43-1.65%, and the 28d compressive strength is 9.54-9.75MPa.
[0096] Compared with Example 1, commercial fly ash is used instead of carboxylated fly ash, then the stone rate is reduced, the water seepage rate is increased, and the compressive strength is reduced (Comparative Example 1); Compared with Example 1, the amount of bisphenol A epoxy resin is changed to 16 parts, and the amount of biphenyl epoxy resin is changed to 4 parts. Due to the excessive amount of bisphenol A epoxy resin, the compounding effect is not good, so the stone rate is reduced, the water seepage rate is increased, and the compressive strength is reduced (Comparative Example 2); Compared with Example 1, the amount of bisphenol A epoxy resin is changed to 4 parts, and the amount of biphenyl epoxy resin is changed to 16 parts. Due to the small amount of bisphenol A epoxy resin, the compounding effect is not good, so the stone rate is reduced. Compared with Example 1, commercially available cyanate ester was used instead of modified cyanate ester, then the stone rate was reduced, the water seepage rate was increased, and the compressive strength was reduced (Comparative Example 4); Compared with Example 1, carbon fiber I was used instead of polydopamine modified carbon fiber, then the stone rate was reduced, the water seepage rate was increased, and the compressive strength was reduced (Comparative Example 5); Compared with Example 1, carbon fiber II was used instead of carbon fiber I to prepare polydopamine modified carbon fiber. Since the diameter of carbon fiber II was too large, the modification effect was not good, so the stone rate was reduced, the water seepage rate was increased, and the compressive strength was reduced (Comparative Example 6).
[0097] In summary, the present invention prepares anti-dispersion shield grouting material by carboxylating fly ash, the main raw material of the grouting material, and introducing modified components such as modified cyanate ester and polydopamine modified carbon fiber, which effectively improves the stone rate of the material, reduces the water bleeding rate, and ensures good compressive strength.
[0098] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing an anti-dispersion shield grouting material, characterized in that: The following steps are involved: Step S1: by weight, 2 to 4 parts of silane coupling agent KH550 and 2 to 4 parts of succinic anhydride are added to 180 to 200 parts of N,N-dimethylformamide and stirred for 2 to 4 hours, then 40 to 50 parts of fly ash are added and stirred for reaction for 4 to 6 hours, and after the reaction is completed, the mixture is dried to obtain carboxylated fly ash; Step S2: adding 160 to 200 parts of cement, 15 to 20 parts of epoxy resin, 4 to 8 parts of cyanate ester and 4 to 6 parts of carbon fiber to 480 to 500 parts of deionized water, stirring for 40 to 60 minutes, and then adding 1 to 3 parts of water reducer, 1 to 3 parts of defoamer, and 0.6 to 0.8 parts of thickener and stirring for 20 to 30 minutes to obtain a premixed system; Step S3: In parts by weight, 360 to 400 parts of the carboxylated fly ash, 100 to 140 parts of mineral powder and 20 to 24 parts of bentonite are added to 480 to 500 parts of the premixed system and stirred to obtain an anti-dispersion shield grouting material.
2. The method for preparing an anti-dispersion shield grouting material according to claim 1, characterized in that: The epoxy resin is bisphenol A type epoxy resin and biphenyl type epoxy resin.
3. The method for preparing an anti-dispersion shield grouting material according to claim 2, characterized in that: The mass ratio of the bisphenol A epoxy resin to the biphenyl epoxy resin is (1-2):
1.
4. The method for preparing an anti-dispersion shield grouting material according to claim 1, characterized in that: The cyanate ester is a modified cyanate ester; The preparation method of the modified cyanate ester comprises: adding 6 to 10 parts of 3-aminopropyltriethoxysilane to 80 to 100 parts of deionized water by weight and stirring evenly, then adding 50 to 60 parts of talc and stirring for 40 to 60 minutes, and drying to obtain modified talc; mixing 90 to 100 parts of cyanate ester, 10 to 12 parts of the modified talc and 4 to 6 parts of ethyl acetate, first stirring and dispersing for 20 to 30 minutes, and then ultrasonically dispersing for 40 to 60 minutes to obtain the modified cyanate ester.
5. The method for preparing an anti-dispersion shield grouting material according to claim 1, characterized in that: The carbon fiber is polydopamine modified carbon fiber; The preparation method of the polydopamine modified carbon fiber comprises: mixing 40 to 50 parts of anhydrous ethanol and 40 to 50 parts of acetone by weight, then adding 10 to 20 parts of carbon fiber and impregnating for 20 to 24 hours, washing with deionized water after the impregnation, and drying to obtain pretreated carbon fiber; adding 16 to 20 parts of trishydroxymethylaminomethane and 6 to 8 parts of dopamine hydrochloride into 300 to 400 parts of deionized water and stirring for 40 to 60 minutes, then adding 10 to 20 parts of the pretreated carbon fiber and soaking for 12 to 16 hours, and vacuum drying after the soaking to obtain the polydopamine modified carbon fiber.
6. The method for preparing an anti-dispersion shield grouting material according to claim 5, characterized in that: The diameter of the carbon fiber is 100-400 nm.
7. The method for preparing an anti-dispersion shield grouting material according to claim 1, characterized in that: The water reducer is selected from any one of polycarboxylate water reducer, melamine water reducer and naphthalene water reducer or a combination of at least two thereof.
8. The method for preparing an anti-dispersion shield grouting material according to claim 1, characterized in that: The defoaming agent is selected from any one of tributyl phosphate, polydimethylsiloxane, and tripolyglycerol monostearate, or a combination of at least two thereof.
9. The method for preparing an anti-dispersion shield grouting material according to claim 1, characterized in that: The thickener is selected from any one of hydroxypropyl methylcellulose, polyvinyl pyrrolidone, and polyacrylamide, or a combination of at least two thereof.
10. The method for preparing an anti-dispersion shield grouting material according to claim 1, characterized in that: The stirring treatment conditions include: stirring at 800-1000 rpm for 10-20 min.
Citation Information
Patent Citations
Vibration-resistant high-toughness shield tunnel synchronous grouting material and preparation method thereof
CN115872676A